A novel legal analysis of Jordanian corporate governance legislation in the age of artificial intelligence - Nasir Albalawee; Amjed Al Fahoum (Cogent Business & Management, 2024)
This scholarly investigation explores the complex correlation between corporate governance and artificial intelligence (AI), recognizing the dynamic nature of the digital revolution. The research consists of two primary interactions: the initial interaction explicates the importance of corporate governance, and the subsequent one examines the incorporation of artificial intelligence applications into governance frameworks. By utilizing a descriptive and analytical approach, this study examines the extent to which current legal frameworks are congruent with the opportunities and challenges presented by digital transformation. The function of AI in reducing the risks associated with unethical financial and managerial practices is a primary concern, as it contributes to the ethical fortification of nations and businesses. The results emphasize the criticality for organizations to strictly comply with governance regulations, highlighting compliance as a fundamental element in demonstrating financial well-being, promoting expansion, and fortifying competitiveness in the corporate sphere. The findings have significant ramifications for both policymakers and organizations. Policymakers and organizations should adopt a proactive strategy to utilize AI's capabilities, improving corporate governance practices and effectively navigating the intricacies of the digital age.
Keywords: 650; Governance; digital transformation; companies leverage; competitive advantage; artificial intelligence